Adoption of sustainable agricultural technologies for vegetable production in rural Tanzania: trade-offs, complementarities and diffusion. Issue 4 (4th July 2022) - Ochieng, Justus; Afari-Sefa, Victor; Muthoni, Francis; Kansiime, Monica; Hoeschle-Zeledon, Irmgard; Bekunda, Mateete; Thomas, Dubois
ABSTRACT: Sustainable agricultural technologies have impacted positively on staple crop yields in Asia and some parts of Sub-Sahara Africa. However, the adoption of similar technologies in vegetable subsector is still low among small-scale farmers in Tanzania. Several efforts aimed at promoting the adoption of the technologies such as improved vegetable varieties, mineral fertilizers, manure and pest management practices to raise output, have not yielded the desired impacts. We examine dynamics of farmers' adoption of these technologies and the factors influencing technology choice. We also predict the peak level and speed of adoption of these sustainable technologies. Findings show that complementarities exist among improved varieties, fertilizers and pest management practices, while tradeoffs exist between manure and mineral fertilizers. These complementarities and tradeoffs should be sufficiently exploited for farmers to adopt technologies that are suited for their specific circumstances. Better knowledge, access to credit, group membership, farmer participation in demonstration trials, and, more substantial livestock holdings drive technology adoption decision. Technologies have different peak levels of adoption, which are reached at different time intervals. The policy option is to strengthen collaborative efforts to scale out sustainable agricultural technologies to respond to the increasing demand for nutrient-dense vegetables for income, food and nutrition security.